Dinner Table Human Capital and Entrepreneurship - Hans K. Hvide; Paul Oyer (Institute of Labor Economics (IZA), 2018)
We document three new facts about entrepreneurship. First, a majority of male entrepreneurs start a firm in the same or a closely related industry as their fathers' industry of employment. Second, this tendency is correlated with intelligence: higher-IQ entrepreneurs are less likely to follow their fathers. Third, an entrepreneur that starts a firm in the same 5-digit industry as where his father was employed tends to outperform entrepreneurs in the same industry whose fathers did not work in that industry. We consider various explanations for these facts and conclude that "dinner table human capital", where children obtain industry knowledge through their parents, is an important factor behind what type of firm is started and how well it performs.
Keywords: J24; L26; 330; entrepreneurship; human capital; IQ